Sex-related macrostructural organization of the deer's brachial plexus - Melo, S. R.; Goncalves, A. F. N.; Sasahara, T. H. de Castro; Fioretto, E. T.; Gerbasi, S. H.; Machado, M. R. F.; Guimaraes, G. C.; Ribeiro, A. A. C. M. (Blackwell Publishing, 2007)
We describe the morphological organization of the deer brachial plexus in order to supply data to veterinary neuroclinics and anaesthesiology. The deer (Mazama gouazoubira) brachial plexus is composed of four roots: three cervical (C6, C7 and C8) and one thoracic (T1). Within each sex group, no variations are observed between the left and the right brachial plexus, though sex-related differences are seen especially in its origin. The origin of axillary and radial nerves was: C6, C7, C8 and T1 in males and C8-T1 (radial nerve) and C7, C8 and T1 (axillary nerve) in females; musculocutaneous nerve was: C6-C7 (males) and C8-T1 (females); median and ulnar nerves was: C8-T1 (males) and T1 (females); long thoracic nerve was: C7 (males) and T1 (females); lateral thoracic nerve was: C6, C7, C8 and T1 (males) and T1 (females); thoracodorsal nerve was: C6, C7, C8 and T1 (males) and C8-T1 (females); suprascapular nerve was: C6-C7 (males) and C6 (females) and subscapular nerve was: C6-C7 (males) and C7 (females). This study suggests that in male deer the origin of the brachial plexus is more cranial than in females and the origin of the brachial plexus is slightly more complex in males, i.e. there is an additional number of roots (from one to three). This sexual dimorphism may be related to specific biomechanical functions of the thoracic limb and electrophysiological studies may be needed to shed light on this morphological feature.